Health-Related Physical Fitness and Academic Performance in Asgori Secondary School, Southwest Shewa Zone, Ethiopia - Ayane, Baharu; Wondirad, Samson; Belachew, Adugna (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
The aim of this study was to determine the relationship between health-related physical fitness and academic performance in Asgori Secondary School. The study was conducted on students of grade 12th of Asgori secondary school, located in Elu Woreda, Southwest Shewa Zone, Ethiopia. This study used cross-sectional research design. The four components (body composition, flexibility, muscular strength and cardiorespiratory endurance) of HRPF were found to have a significant impact on students’ academic performance. The cardiovascular endurance (2-mile running) and muscular strength (push-up test) of the students have been found to positively influenced the academic performance (P < 0.05). This study suggests that cardiovascular endurance and muscle strength of students are found to be significantly impacting students’ performance.